Pengembangan Model Evaluasi dalam Penguatan Ideologi Pendidikan Sekolah Dasar - Magdalena, Ina; Nurchayati, Aan; Safitri, Agustini (Lembaga Yasin AlSys, 2023)
This article was written using the meta-analysis method. This type of research used qualitative research. This research was conducted to find out how far character education is carried out in learning, especially elementary schools. With the progress of the times with educational ideologies. The evaluation model is also very much needed in the world of education to form superior quality ideologies that foster a sense of responsible attitude in dealing with the world of education. Because the evaluation model in strengthening educational ideology can optimize the development of the dimensions of the nation's children and can form and develop people who are devoted to God Almighty, comply with applicable legal rules, interact between cultures, apply noble values, morals and ethics as the pride of the Indonesian people.